2018
DOI: 10.4300/jgme-d-17-00590.1
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Feedback to Individual Residents: An Examination of Preceptor Challenges and Approaches

Abstract: Examining the feedback challenges preceptors encounter and the approaches taken to adapt feedback to individual residents can provide insight into how preceptors meet the challenges of competency-based medical education, in which frequent, focused feedback is essential for residents to achieve educational milestones and entrustable professional activity expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Faculty agreed that the cocky resident needed confronting, the defensive resident needed specific examples, and the self-effacing resident needed exploration and support. This closely echoes the findings of Roze des Ordons, Cheng, Gaudet, Downar, and Lockyer, 22 who explored the challenges that faculty experienced and the approaches taken in adapting feedback conversations to different residents. While the faculty questioned their ability, they were able to adapt their approach to feedback, drawing on techniques of coaching for highly performing residents, directing for residents demonstrating insight gaps, mentoring and support for emotionally distressed residents, and mediation for overly confident residents.…”
Section: Discussionsupporting
confidence: 77%
“…Faculty agreed that the cocky resident needed confronting, the defensive resident needed specific examples, and the self-effacing resident needed exploration and support. This closely echoes the findings of Roze des Ordons, Cheng, Gaudet, Downar, and Lockyer, 22 who explored the challenges that faculty experienced and the approaches taken in adapting feedback conversations to different residents. While the faculty questioned their ability, they were able to adapt their approach to feedback, drawing on techniques of coaching for highly performing residents, directing for residents demonstrating insight gaps, mentoring and support for emotionally distressed residents, and mediation for overly confident residents.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with the medical education literature, the findings of this study broadly show that written preceptor feedback is being provided across all EPAs and comprehensively included positive, neutral, and negative feedback. 7,8,9 Further, while feedback varied in meeting the 'optimal feedback' definitions recommended by scholars in the learning sciences, key opportunities identified for preceptor development include the provision of directional, goal-oriented skill-specific feedback. This study is a first-step in highlighting a potential area of opportunity to enhance preceptor-provided written feedback on EPAs in pharmacy curricula.…”
Section: Discussionmentioning
confidence: 99%
“…Roze des Ordons and colleagues studied medical resident preceptors who reported feeling uncertain regarding how to individualize feedback, navigate tensions between resident and preceptoridentified goals, as well as how to coach residents with insight gaps and mediate overly confident residents. 8 Additionally, preceptors may have felt less certain on how to tailor the set level of EPA entrustment to their unique practice setting and specialty. In a study conducted by Moon and colleagues, preceptors reported being less certain of what the EPA entrustment level should be to consider an objective or skill achieved for residency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, coaching techniques could be used for highly performing residents, a more directive approach in those with insight gaps, mediation for overly confident residents, and mentoring for those with emotional distress. 32 Regardless of the exact model of feedback used by an individual or a group, a positive institutional feedback culture is important and should be promoted. 33 Some general principles in cultivating such a positive feedback culture include creating a respectful, friendly, and unthreatening climate, eliciting trainees' thoughts, staying nonjudgmental, focusing on behaviors, basing feedback on observed facts, being specific, suggesting ideas for improvement, and determining welldefined, negotiated goals.…”
Section: Feedbackmentioning
confidence: 99%